RS1 gene is a novel prognostic biomarker for lung adenocarcinoma. Issue 12 (15th May 2022) - Zhang, Tao; Cheng, Guowei; Chen, Ping; Peng, Yue; Liu, Lei; Li, Runze; Qiu, Bin
Abstract: Background: Although it has a poor prognosis, patients with lung adenocarcinoma (LUAD) have a relatively higher 5‐year survival period. Thus, it is necessary to identify effective prognostic markers to evaluate the effect of early treatment. RS1 gene encodes retinoschisin, a key protein in congenital retinoschisis, while few studies have been reported on the association between RS1 and cancer prognosis. Methods: We performed bioinformatic analyses based on the data obtained from The Cancer Genome Atlas and Gene Expression Omnibus databases to demonstrate the expression level of RS1 was related to the LUAD prognosis and our findings were verified in‐vitro and clinical samples. Then, we explored the potential mechanism of how RS1 expression influenced the prognosis of LUAD. Results: Compared with normal tissues, the RS1 expression was significantly lower in tumor tissues. The Multivariate Cox regression model showed that RS1 could be used as an independent prognostic indicator. Furthermore, we found significant differences in immune cell infiltration between RS1 high and low expression groups, and the proteasome pathway was found enriched in RS1 low expression samples. Conclusion: In conclusion, our study suggests that RS1 is a novel prognostic biomarker for LUAD. Differences in immune cell infiltration and signaling pathways may contribute to the poor prognosis of LUAD caused by low RS1 expression. Abstract : In our study, based on gene expression profiling analysis of the TCGA and GEO databases, we demonstrated that the expression level of RS1 gene was related to the prognosis of LUAD and low expression of RS1 could be used as an independent prognostic indicator for LUAD. Further enrichment analyses indicated that low expression of RS1 was associated with the proteasome signaling pathway in LUAD.